2018
DOI: 10.1200/jco.2018.36.18_suppl.lba4002
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative chemoradiotherapy versus immediate surgery for resectable and borderline resectable pancreatic cancer (PREOPANC-1): A randomized, controlled, multicenter phase III trial.

Abstract: LBA4002 Background: Standard of care for patients with (borderline) resectable pancreatic adenocarcinoma is resection followed by adjuvant chemotherapy. Previous studies suggest a benefit of neoadjuvant treatment. We conducted a multicenter phase III randomized controlled trial to evaluate the effect of preoperative chemoradiotherapy. Methods: Patients with (borderline) resectable pancreatic cancer, pathologically confirmed, were randomized between immediate surgery (arm A) and preoperative chemoradiotherapy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
95
0
5

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(101 citation statements)
references
References 0 publications
1
95
0
5
Order By: Relevance
“…Additional subanalysis demonstrated increased mortality in patients who did not receive preoperative chemotherapy. This finding is consistent with the preliminary result of the recent phase III PREOPANC‐1 trial that preoperative treatment improves outcomes in resectable pancreatic cancer …”
Section: Discussionsupporting
confidence: 90%
“…Additional subanalysis demonstrated increased mortality in patients who did not receive preoperative chemotherapy. This finding is consistent with the preliminary result of the recent phase III PREOPANC‐1 trial that preoperative treatment improves outcomes in resectable pancreatic cancer …”
Section: Discussionsupporting
confidence: 90%
“…It demonstrated prolonged rates of OS, disease‐free survival, distant metastasis‐free survival, locoregional relapse‐free survival, and R0 resection rates. The PRODIGE 24 study achieved median OS rates of 54.4 months with modified adjuvant FOLFIRINOX in selected patients after excellent surgical recovery …”
Section: Discussionmentioning
confidence: 99%
“…Van Tienhoven et al conducted an RCT of NACRT for R and BR PDAC (PREOPANC‐1 trial). Their preliminary results showed an improved trend in OS by NACRT, but it was not significant . Several secondary endpoints were shown to be in favour of NACRT, including the R0 resection rate and disease‐free survival.…”
Section: Randomized Controlled Trialsmentioning
confidence: 98%
“…The reduction of hepatic relapse after surgery with NAC might suggest that pre‐operative systemic delivery of combination chemotherapy would be necessary to impede the progression of micrometastases even in R PDAC, providing long‐term survival. The low resection rate of NACRT might be partly because previous studies used a reduced dose of systemic chemotherapy in combination with radiotherapy. Katz et al reported the feasibility and efficacy of NAC FOLFIRINOX followed by NACRT for BR PDAC in multi‐institutional trials.…”
Section: Chemotherapy And/or Radiotherapy?mentioning
confidence: 99%